Caterer two charges 550 for hall rental plus $40 per person
Answer:
=(x-2)/3(x+4)
Step-by-step explanation:
F(x)=x²-3x+2/3x²+9x-12
Using mid term break formula
=x²-2x-x+2/3(x²+3x-4)
=x(x-2)-1(x-2)/3(x²+4x-x-4)
=(x-2)(x-1)/3{x(x+4)-1(x+4)}
=(x-2)(x-1)/3(x-1)(x+4)
Cancelling (x-1)
We get
=(x-2)/3(x+4)
Hope it helps :)
Answer:
<em>As </em><em>we </em><em>know </em><em>that </em><em>there </em><em>is </em><em>a </em><em>radius </em><em>which </em><em>is </em><em>2 </em><em>cm</em>
<em>so </em>
<em>circumference </em><em>=</em><em> </em><em>2</em><em> </em><em>π</em><em> </em><em>r</em>
<em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>=</em><em> </em><em>2</em><em> </em><em>*</em><em> </em><em>2</em><em>2</em><em>/</em><em>7</em><em> </em><em>*</em><em> </em><em>2</em>
<em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>=</em><em> </em><em>1</em><em>2</em><em>.</em><em>5</em><em>7</em><em>c</em><em>m</em>
<em>it's </em><em>circumference </em><em>is </em><em>1</em><em>2</em><em>.</em><em>5</em><em>7</em><em> </em><em>cm</em>
Answer:
Missing length = 20
Step-by-step explanation:
Ratio is 16/20=4/5
25×4/5=20
Answer: Variant C
Step-by-step explanation:
f(x) = 3x^2 − 4
For finding f(-2) just replace x with - 2 like this:
f(-2)=3*((-2))^2-4=3*4-4=12-4=8